Characterization of PTW-31015 PinPoint ionization chambers in photon and proton beams. (19th September 2018) - Carlino, A; Stock, M; Zagler, N; Marrale, M; Osorio, J; Vatnitsky, S; Palmans, H
Abstract: The increased use of complex forms of radiotherapy using small-field photon and proton beams has invoked a growing interest in the use of micro-ionization chambers. In this study, 48 PTW-TM31015 PinPoint-type micro-ionization chambers that are used in the commissioning and patient specific QA of a proton pencil beam scanning (PBS) delivery system have been characterized in proton and high-energy photon beams. In both beam modalities, the entire set of PinPoint chambers was characterized by imaging them, by evaluating their stability using check source measurements, by experimentally determining the ion recombination, polarity effect and by cross calibrating them in terms of absorbed dose to water against Farmer-type ionization chambers. Beam quality correction factors were theoretically derived for both beam modalities. None of the chambers' check source readings drifted by more than 0.5% over a one year period. Beam quality correction factors for the 6 MV photon with reference to 60 Co were on average 1.0 ± 0.5% lower than the theoretical values calculated according to the data and procedures outlined in IAEA TRS-398. While this difference is within the overall dosimetric uncertainty, it is significant considering only uncorrelated uncertainties indicating inconsistencies in the theoretical data. Beam quality correction factors for the 179.2 MeV proton beam with reference to 60 Co were in good agreement with the theoretical data. Ion recombination and polarity correction factors were very consistent for all chambers with standard deviations of 0.2% or below show that findings from more comprehensive investigations in the literature can be considered as representative for all the chambers of this type. The characterization of 48 PinPoint-type micro-ionization chambers performed in this study provided a unique opportunity to investigate chamber-to-chamber variations of calibration, beam quality correction factors, ion recombination and polarity correction factors for an unprecedented sample size of chambers for both high-energy photon and proton beams.